DUALITY ORGANIZATION AND CORPORATE ADAPTATION DUALITE ORGANISATION ET ADAPTATION D’ENTREPRISE - عميار, حبيب (جامعة مسيلة, 2018)
Many challenges await Algerian companies in the current complex and unfavorable environment, mainly since the lifting of tariff barriers and the intensification of international competition that do not allow them, in their current modes of organization and management, even after the adjustment and upgrading programs, which have benefited, and despite the experience and dedication of managers, to remain profitable on the market. It is essential to raise the entrepreneur's awareness of the need for redeployment for continuous adaptation, with regard to future challenges through an efficient "Strategic Steering" of its activities, a delegation of responsibilities and better distribution of tasks.
Keywords: Redeployment, change, adaptation, strategic diagnosis, adjustment and reorientation.